Courtney Crumrin. Volume 7, Tales of a warlock - Naifeh, Ted (Oni Press, 2015)
Though the Witches and Warlocks of Hillsborough keep to themselves under Ravenna's Law, there are outliers who are a danger to others. The Anti-Sorcery Society, headed by mortal Horace Crisp, seeks to destroy these individuals, and Aloysius Crumrin, an eager young man, offers his assistance -- keeping his magical ancestry to himself, of course. But he doesn't count on Alice Crisp, Horace's tenacious daughter, accompanying him on missions, or on trusting her with his secret -- or on falling in love. Which proves more dangerous than anything when Horace becomes his enemy.